Application of Murabahah Financing with Debt Transfer (Take Over) in Islamic Banking in Indonesia - Utomo, Hery Dwi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The level of public trust in the performance of Islamic banking is quite rapid. One of them is because it is based on the principle of ta'āwun (helping and cooperation among people for good and benefit) which is in accordance with the ethnographic conditions of the Muslim population in Indonesia. From the author's observation, the need for (take over) Home Ownership Loans is increasing from conventional banks to Islamic banking. The author highlights the debt transfer financing contract (take over) carried out by Islamic banking with the concept of ta'awun. This research uses empirical research to examine and analyze the implementation and application of law in society and sociological research, to look at law from the point of view of formal institutions and understand the law and the empirical behavior of applicable legal operations. the approach used socio legal research. The application of murabahah financing, one of the financing with the principle of sale and purchase (ba'i) in Islamic banking, provides many benefits for lighter installments for customers.